Plant Viruses: From Targets to Tools for CRISPR - Varanda, Carla M. R. (Viruses, 2021)
Plant viruses cause devastating diseases in many agriculture systems, being a serious threat for the provision of adequate nourishment to a continuous growing population. At the present, there are no chemical products that directly target the viruses, and their control rely mainly on preventive sanitary measures to reduce viral infections that, although important, have proved to be far from enough. The current most effective and sustainable solution is the use of virus-resistant varieties, but which require too much work and time to obtain. In the recent years, the versatile gene editing technology known as CRISPR/Cas has simplified the engineering of crops and has successfully been used for the development of viral resistant plants. CRISPR stands for ‘clustered regularly interspaced short palindromic repeats’ and CRISPR-associated (Cas) proteins, and is based on a natural adaptive immune system that most archaeal and some bacterial species present to defend themselves against invading bacteriophages. Plant viral resistance using CRISPR/Cas technology can been achieved either through manipulation of plant genome (plant-mediated resistance), by mutating host factors required for viral infection; or through manipulation of virus genome (virus-mediated resistance), for which CRISPR/Cas systems must specifically target and cleave viral DNA or RNA. Viruses present an efficient machinery and comprehensive genome structure and, in a different, beneficial perspective, they have been used as biotechnological tools in several areas such as medicine, materials industry, and agriculture with several purposes. Due to all this potential, it is not surprising that viruses have also been used as vectors for CRISPR technology; namely, to deliver CRISPR components into plants, a crucial step for the success of CRISPR technology. Here we discuss the basic principles of CRISPR/Cas technology, with a special focus on the advances of CRISPR/Cas to engineer plant resistance against DNA and RNA viruses. We also describe several strategies for the delivery of these systems into plant cells, focusing on the advantages and disadvantages of the use of plant viruses as vectors. We conclude by discussing some of the constrains faced by the application of CRISPR/Cas technology in agriculture and future prospects.